Pembahasan Kilat Undang-Undang Nomor 3 Tahun 2022 tentang Ibu Kota Negara di Era Rezim Presiden Joko Widodo - Hoshi Rahma Saraswati (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
This study aims to examine the process of enacting Law Number 3 of 2022 concerning the Capital City, which was completed in a relatively short period of only 42 days. The main focus of this research is to assess whether the legislative process was in accordance with the principles of proper law-making as stipulated in Law Number 12 of 2011 on the Formation of Laws and Regulations. This study employs a normative legal research method with a literature-based approach, relying on the analysis of legislation, legal literature, and relevant official documents. The findings indicate that the drafting process of the Capital City Law was conducted hastily and did not fully comply with the applicable provisions. This is reflected in the limited public participation, the lack of transparency in the deliberation, and the absence of democratic principles that should guide the law-making process. The fact that the bill was deliberated in only 42 days demonstrates a legislative process that was neither ideal nor substantive in nature. Moreover, the accelerated process tends to reflect a conservative and elitist character, in which the aspirations of the wider community were insufficiently accommodated. In conclusion, the enactment of Law Number 3 of 2022 cannot be considered ideal from the perspective of constitutional law or democratic principles. Therefore, it is necessary to evaluate and reform legislative mechanisms to ensure that future law-making processes are more participatory, transparent, and truly reflective of the interests of the people.